Cognitive processing influences postural control during quiet standing - Dault, Mylène Claude (University of Waterloo, 2001)
Performance of concurrent activities is required in many of our daily activities. It therefore is critical to determine how postural control and cognitive processing interact. Results from previous studies have found that postural control and tasks requiring cognitive processing influence each other; however, results are inconsistent. Some studies showed increased postural sway while others showed decreased or no change in postural sway when individuals were asked to perform a cognitive task. Hence, this thesis proposes to investigate how and why postural control and various cognitive processes influence each other. A series of five studies were conducted to address this issue. For all five studies presented in this thesis, participants were asked to perform various tasks requiring cognitive processing while standing on a force platform that monitored their centre of pressure (COP) displacements. COP displacement provides information on the control of posture since it is closely related to the center of mass (COM) displacements. The length of the trials and the postural sway measures were constant across all studies to allow comparison of the different manipulations of the cognitive tasks. Results from all studies presented in this thesis indicated that young healthy participants increase frequency and decrease amplitude of COP displacement. These change sin postural control occurred in all studies regardless of the type of the cognitive task, instructions to stand as still as possible, the motor and sensory requirements of the cognitive task and practice. The final study investigated how the elderly were able to control posture while performing a cognitive task; results indicated that they responded differently than young individuals by increasing both amplitude and frequency of COP displacement in only the medio-lateral direction. Hence, the lack of consistency of results reported by previous studies may be attributed to various trial lengths and measures of postural control, the difficulty of the postural task, as well as age and pathology and not to the characteristics of the cognitive task. During quiet standing, young individuals consistently increased joint stiffness when performing a concurrent task. Increased stiffness control may allow the operational demands on the CNS to be reduced which allows young individuals to perform a cognitive task without being at greater risk of falling. On the other hand, elderly and pathological populations may not have the ability to control posture in the same manner, which may lead to greater risk of falling when in a dual-task situation.
Keywords: Harvested from Collections Canada